The Case of a Primary Tuberculosis Complex in a Child With Late Detection - Irina Yu. Petrakova; Marina F. Gubkina; Yury S. Berezovsky; Mamed A. Bagirov; Bagirov V. Yukhimenko (Вопросы современной педиатрии)
We present a case of late detection and course of the primary tuberculosis complex in a child who was previously in an unknown contact with a tuberculosis patient at the first year of life. The  disease onset simulating pneumonia took place at the age of 1 year  8 months. Hereafter, the child did not have any clinical signs of the  disease. At the age of 5 years, the child was examined in connection  with the hyperergic reaction to tuberculin: the results of computed  tomography revealed calcinated foci in the lung tissue and  calcifications in the intrathoracic lymph nodes; bronchoscopy  revealed infiltrative bronchial tuberculosis. Surgery was performed:  video-assisted thoracoscopy, resection of C9,10 part of the left lung  with precision removal of the focus in its C6 segment, extirpation of  bifurcation, and left bronchopulmonary lymph nodes. The results of  the histological examination indicated the chronic course of the  tuberculosis process with formation of bronchiectasis and presence  of bronchonodular fistulas. After surgery and the main course of  antituberculous therapy, a clinical cure with small residual changes was achieved.